2019
DOI: 10.1126/scisignal.aat7397
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin 2 regulates mitochondrial Ca 2+ signaling, bioenergetics, and dynamics through mitofusin 2

Abstract: Mitochondria and the endoplasmic reticulum (ER) have an intimate functional relationship due to tethering proteins that bring their membranes in close (~30 nm) apposition. One function of this inter-organellar junction is to increase the efficiency of Ca2+ transfer into mitochondria, thus stimulating mitochondrial respiration. Here we show that the ER cation-permeant channel polycystin 2 (PC2) functions to reduce mitochondria-ER contacts. In cell culture models, PC2 knockdown led to a 50% increase in mitofusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 87 publications
(113 reference statements)
1
64
0
2
Order By: Relevance
“…While all the data reported to date in cellular and animal models carrying Pkd1 mutations provide a unified evidence of reduced mitochondrial calcium uptake, reduced mitochondria biogenesis, and reduced mitochondrial function, one recent study seems to suggest that the opposite occurs in Pkd2 mutants. Indeed, increased MAM contacts, increased calcium uptake, increased mitochondrial activity (oxygen consumption rate) were all reported in Pkd2 cellular and animal models, all effects mediated by an increase in MFN2 expression 13 . Here, we show that on the contrary, Pkd1 mutants do not have increased MFN2 levels, in line with a previous study showing decreased Ca 2+ uptake in the mitochondria 9 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While all the data reported to date in cellular and animal models carrying Pkd1 mutations provide a unified evidence of reduced mitochondrial calcium uptake, reduced mitochondria biogenesis, and reduced mitochondrial function, one recent study seems to suggest that the opposite occurs in Pkd2 mutants. Indeed, increased MAM contacts, increased calcium uptake, increased mitochondrial activity (oxygen consumption rate) were all reported in Pkd2 cellular and animal models, all effects mediated by an increase in MFN2 expression 13 . Here, we show that on the contrary, Pkd1 mutants do not have increased MFN2 levels, in line with a previous study showing decreased Ca 2+ uptake in the mitochondria 9 .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our data indicate a downregulation of pro‐fusion proteins OPA1 and MFN1 and a reduction in mitochondrial mass. Of interest, we did not observe any decrease in the expression levels of MFN2 (Figure S3), a molecule that is relevant not only for mitochondrial fusion, but also for tethering of the ER membrane to mitochondria, being it localized also on the ER side 13 . These data further highlight that the increase in DRP1 is not secondary to mitochondria alterations and it is very likely to contribute and sustain the increase in mitochondrial fragmentation.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Transmission of calcium into mitochondria depends on which ITPR isoforms are expressed at the MAM, ( 15,16 ) which varies among cell types and can change in disease states. ( 13,14,17,18 ) Therefore, we examined whether expression of each of the three ITPR isoforms was altered in YF.…”
Section: Resultsmentioning
confidence: 99%
“…ITPR2 can preferentially transmit calcium into mitochondria in some cell types, ( 15,40 ) and ITPR2 expression was increased in YFV‐infected hepatocytes, but there is disagreement about whether this isoform localizes to the MAM and does not regulate steatosis in hepatocytes. ( 14,41 ) ITPR3 can preferentially transmit calcium into mitochondria in other cell types ( 15‐17,42 ) . Indeed, we found that loss of ITPR3 sensitized YFV‐infected cells to apoptosis; however, effects of ITPR3 on steatosis may instead reflect concomitant changes in expression of enzymes involved in fatty acid oxidation and lipogenesis.…”
Section: Discussionmentioning
confidence: 99%